The effect of a carbon layer on the microstructural and mechanical properties of porous BN/Si3N4 ceramic brazed with a titanium-silicon filler. Issue 4 (April 2018) - Zhuang, Y.L.; Lin, T.S.; Wang, S.J.; He, P.; Sekulic, D.P.; Jia, D.C.
Abstract: The Ti22 Si78 (wt.%) braze was used to bond porous BN/Si3 N4 ceramic. The results revealed that the joint strength was low. In order to improve the joint strength, a carbon coated modification of the porous BN/Si3 N4 substrate, achieved by the pyrolysis of phenol-formaldehyde resin was suggested. The thickness of carbon layer was controlled by the volume ratio of phenol-formaldehyde resin and methyl alcohol (R/M). The effect of the carbon layer on the microstructure and mechanical properties of the joint was examined. It was established that the maximum joint strength was achieved at the level of 80 MPa (as opposed to the uncoated joint with only 30 MPa) when R/M was 1:2, at the given brazing temperature. The improvement of the joint strength is attributed mainly to the formation of a SiC infiltration reaction layer, a significant population of SiC nanowires, as well as TiN0.7 C0.3 and TiB2 particles.